Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Melyn Konveksi - Lena Agustina; Arga Sutrisna; Dudu Risana (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research took place at Melyn Konveksi and aims to determine the influence of the Work Environment and Work Motivation on Employee Performance among Melyn Konveksi employees. This research involved the use of survey methods with a quantitative approach, the sample used was 40 people aged 18-50 years who worked at Melyn Konveksi. Data processing is carried out from primary and secondary data sources. The research data was then processed by testing validity and reliability, classical assumption testing, statistical analysis testing, and hypothesis testing using the SPSS Version 25 application. Based on the F test, it shows that the Work Environment and Work Motivation simultaneously do not significantly influence Employee Performance. The results of the T test show that the Work Environment and Work Motivation do not partially influence employee performance significantly.